Analisis Pengaruh Foreign Direct Investment dan Perdagangan Internasional Terhadap Penyerapan Tenaga Kerja Di Asean-5 - Gaillardia Arifa Almas (Warta Pendidikan | e-Journal, 2021)
The purpose of this research is to determine the effect of Foreign Direct Investment and International Trade (Export-Import) on Labor Absorption in ASEAN-5. By using a quantitative approach. The analytical tool used is panel data regression analysis with the Fixed Effect Model approach using Eviews 9 software. With this analysis, the results obtained if the variables of Foreign Direct Investment in ASEAN-5 countries and Export and Import have a significant effect simultaneously with the independent variables contributing 93.1 % of the dependent variable, while the remaining 6.9% is explained by other variables not included in this study. The partial test results show that the value of Foreign Direct Investment, Exports and Imports in ASEAN-5 has a significant positive effect on the value of Labor Absorption in ASEAN-5 Countries.